Nutritional intake of elite football referees - Teixeira, V. H.; Gonçalves, L.; Meneses, T.; Moreira, P. (Journal of Sports Sciences, 2014)
There is a paucity of dietary data in football referees. In this study, 23 elite main and assistant referees (34.4 ± 5.6 years) completed a 7-day dietary record during the competitive season. No nutritional intake differences were observed between main and assistant referees. Referees` mean daily energy intake (DEI) was 2819 ± 279 kcal. The intake of proteins (1.7 ± 0.2 g/kg), carbohydrates (4.1 ± 0.8 g/kg) and fats (1.4 ± 0.2 g/kg) represented, respectively, 18.4 ± 1.5%, 44.4 ± 4.4% and 34.6 ± 4.1% of the DEI. Carbohydrate intakes before, during and after exercise were 66 ± 42, 7 ± 15 and 120 ± 62 g. Daily carbohydrate, fibre, polyunsaturated fat and water intakes were below recommendations, while fat, saturated fat, cholesterol and sodium intakes were above recommended values. The prevalence of inadequate intake was high for vitamin E (96%), folate (74%), vitamin A (61%), vitamin C (39%), magnesium (26%) and calcium (22%). Carbohydrate intake before, during and after exercise were far from achieving the minimum recommended values. Most referees demonstrated a negligent behaviour of hydration during exercise. Referees would benefit from dietary education in order to optimise performance and health.